Food Safety for Animal Products: The Need in The International Free Trade - Sjamsul Bahri; Indraningsih .; R Widiastuti; T B Murdiati; R Maryam (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2002)
Issues of food safety, includes the food safety for the animal products grows to inhibit the incoming of low quality imported animal product which is unsafe for human being. Therefore several countries enhance to produce high quality of animal product and safe to be consumed. This paper reviews several factors that distribute to the quality and food safety in every single chain of the preparation of animal products. In pre-production step, many factors involve to the quality and safety because several contaminants and diseases can be happened in this step. Several data of diseases and contaminants which causes the negative impacts on economic, political and health will be provided in this paper. An effort to produce high quality and safe animal products can be done by implementing the HACCP in every step of preparation of it (GAP, GHP, GMP, GDP, and GRP). To assure the distribution of high quality and halal of imported animal products in Indonesia, it is necessary to give more strict regulation which is supported by infrastructure, facilities, human resources development and law enforcement.   Key words: Food safety, animal products, international free trade, HACCP